Using of Hantzsch Condensation Reaction in Spectrophotometric Determination of Benzocaine - Mohammed M. Mohammed; Nabeel S. Othman; Faiz M. Al-Abady (Tikrit Journal of Pure Science, 2021)
An accurate spectrophotometric method had been suggested for the determination of benzocaine (BEN) as pure form and in its pharmaceutical preparation (ear drop). The method depends on using Hantzsch reaction, the reaction included condensation of Benz with acetyl acetone-formaldehyde (Ac-Ac-FD) reagent. The suggested reagent was prepared by the reaction of Ac-Ac with FD, the reaction requires heating in a water bath at boiling point for 5 minutes. The condensation of BEN with Ac-Ac-FD needs heating in a water bath at a temperature of 400C for 25 minute, an intense yellow colored product was formed, which is stable and water-soluble. The yellow product has a maximum absorption at 417 nm. The linearity of Beer's law was observed within the range (2-48 μg BEN.ml-1).The values of a molar absorptivity of 1.82x103 l.mol-1.cm-1 and Sandell's sensitivity index values of 0.0907μg .cm-2.The relative error, relative standard deviation, low detection limit and low of quantitation values have been estimated. An application part of the suggested method in estimation of Benz in ear drop (otocol drops).